Piscivore water bird diversity at freshwater tributaries of Zambezi River, Namibia - Lucas P. Rutina; Evans Simasiku; Joseph M. Kabanze (Koedoe: African Protected Area Conservation and Science)
Piscivorous waterbirds enhance wetlands’ diversity and have been seen as bio-indicators of ecological conditions within ecosystems. In addition to their ecological contribution, to wetlands functions and ecosystem services, these birds have been reported to be affected by fishing activities and to compete with fisheries. Despite their importance along wetlands, their populations are in serious decline on a global level. This study aimed at comparing piscivorous waterbirds community composition and functional diversity between a fish protected area (FPA) and a non-fish protected area (NFPA) in two tributaries of Zambezi River in Namibia. At each site, all the waterbirds within a radius of 50 metres were enumerated and identified using binoculars and guide books. For each tributary, species diversity, taxonomic diversity, functional diversity, and community-based trait diversity indices were calculated. A total of 40 carnivorous waterbirds species belonging to 9 orders were recorded during the survey. Of these 40 species, 10 (25%) predominantly feed on fish, 6 (15%) predominantly feed on insects and 24 (60%) species predominantly feed on both fish and insects. At the FPAs site, a total of 35 species were recorded, comprising 10 (29%) species that predominantly feed on fish, 4 (11%) species that predominantly feed on insects and 21 (60%) species that feed on both fish and insects. Generally, piscivorous waterbirds species diversities were not significantly different between a FPA and a NFPA (p  0.05). However, all piscivorous waterbirds functional diversities indices calculated were significantly different between FPAs and NFPAs (p  0.05).